Autonomía económica de cinco mujeres del área rural perteneciente de la asociación de mujeres emprendedoras San Nicolás. - García Segura, María Vanessa (Universidad Antonio Nariño, 2023)
The present research work arose with the idea of What are the economic characteristics that determine the economy of five rural women belonging to the Association of enterprising women of San Nicolás? The general objective was to determine some of the economic characteristics that define the economy of five rural women belonging to the Association of enterprising women of San Nicolás and their relationship with their economic autonomy. The specific objectives were to describe some of the economic characteristics of rural women belonging to the Association of enterprising women of San Nicolás; to analyze the most evident economic practices of rural women belonging to the Association of enterprising women of San Nicolás; to determine the most significant characteristics of the economy of rural women belonging to the Association of enterprising women of San Nicolás and their relationship with their autonomy.